ADAPTIVE LEARNING OF SUNDANESE SCRIPT BASED ON ANDROID GAMES IN THE DIGITAL ERA - Wulandari, Linda Sari; Rosalina, Erlyn; Shomami, Amalina (P2M STKIP Siliwangi, 2023)
Based on the vitality of the language, Sundanese is still classified as safe because it is still used in daily communication from children to the elderly. However, it is different from the use of the Sundanese Script. This study aims to provide solutions and innovations in the Sundanese Script learning model. This study uses a qualitative method. Data collection techniques using observation and performance tests using a digital Sundanese Script flashcard based on Android Quizlet. Data analysis was analyzed descriptively. The results showed that digital Sundanese Script flashcards can be played by students through the Quizlet android-based application so that teachers can design various forms of Sundanese Script flashcard games via smartphones and know the progress of learning outcomes dynamically in a sustainable manner. This learning model is needed for language learning and adaptive Sundanese Script learning in the digital era for Z generation. The students feel more comfortable learning Sundanese Script using Quizlet games in various modes, such as flashcards mode, learn (fast learning) mode, memorize mode, learn-apply mode, match mode, and test mode. When compared to conventional methods, learning language (Sundanese Scripts) using Quizlet is more acceptable to students who are Generation Z.